Elementary School Teachers' Perceptions of the Effectiveness of PBL in Merdeka Curriculum Learning - Sagaf S. Pettalongi (PT. Anagata Sembagi Education, 2025)
The implementation of Problem-Based Learning (PBL) within the Merdeka Curriculum requires elementary school teachers to assume more active, reflective, and facilitative roles. However, the effectiveness of PBL is strongly influenced by teachers’ perceptions of its relevance, practicality, and learning impact. This study analyzes elementary school teachers’ perceptions of PBL effectiveness using a descriptive qualitative method through a systematic narrative review. Literature identification, screening, and eligibility assessment followed a PRISMA-based process, resulting in 26 relevant sources for analysis. The findings reveal that teachers’ perceptions are shaped by conceptual understanding, prior experience, ability to design authentic problems, and the level of support provided by the school environment. Positive perceptions lead to more consistent implementation, whereas negative perceptions are commonly associated with time constraints, limited resources, and insufficient training. The discussion highlights several strategies to strengthen PBL effectiveness, including practice-oriented professional development, collaborative planning, authentic assessment, and supportive school leadership. This study concludes that teachers’ perceptions are a key determinant of successful PBL implementation and must be strengthened through systemic interventions to ensure effective and sustainable learning within the Merdeka Curriculum.